The Hietzing Years. Issue 1 (1st January 2018) - Danto, Elizabeth Ann
ABSTRACT: In the field of psychoanalytic pedagogy of the late 1920s, Anna Freud and Dorothy Tiffany Burlingham were the pacesetters. They launched the Hietzing School during Vienna's years of remarkable strides in social welfare, cultural innovation, and concurrently advancing fascism. Along with Erik H. Erikson, Peter Blos, August Aichhorn, and Eva Rosenfeld–among others–in a log cabin built in a suburban backyard, they crafted a new pedagogy for the modern child in the context of individual and group development. The small school led to further Freud–Burlingham endeavors, including the Jackson Nursery in Vienna, and the Hampstead War Nurseries and the Hampstead Child Therapy Course and Clinic in London. Arguably more valuable, however, are the many theories that emerged from the school: child analysis, psychoanalytic pedagogy, self-regulation, adolescent psychology, self and identity. Endearingly called the "Matchbox School" by its students and faculty, the Hietzing School closed in 1932, yet it left an outstanding institutional and conceptual legacy with which we are still working today.